2020
DOI: 10.1016/s2215-0366(19)30525-5
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Northern Ireland: epidemiology, risk factors, and prevention

Abstract: The rates of suicide and self-harm in Northern Ireland have increased markedly from 2004 to 2019, with a particularly striking increase from 143 registered suicides in 1996 to 305 in 2017. This review summarises the epidemiology of suicidal behaviour, as well as the evidence from a small number of studies that have identified risk factors associated with the high suicide rates here. These were mental illness, trauma, exposure to the conflict, deprivation, relationship problems, employment difficulties, financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 79 publications
(88 reference statements)
5
20
0
1
Order By: Relevance
“…Psychological illness is another input feature in three prediction systems that could predict suicide ideation/behavior. This is in line with previous studies that found a strong relationship between psychological distress and suicide ideation [ 85 , 90 , 91 , 92 ]. In our study, the main psychological problems that could predict suicide ideation/behavior were depression, anxiety, and obsessive-compulsive disorder.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Psychological illness is another input feature in three prediction systems that could predict suicide ideation/behavior. This is in line with previous studies that found a strong relationship between psychological distress and suicide ideation [ 85 , 90 , 91 , 92 ]. In our study, the main psychological problems that could predict suicide ideation/behavior were depression, anxiety, and obsessive-compulsive disorder.…”
Section: Discussionsupporting
confidence: 93%
“…The main items here were the type of exposure to trauma (first-hand or witnessing trauma) and PTSD symptoms. These findings complement previous findings showing that there is a strong link between trauma exposure and suicide risk [ 15 , 16 , 17 , 18 , 36 , 85 , 86 ]. PTSD symptoms such as cognitive distortion, irritability, and an intense feeling of distress when reminded of the traumatic event were the main variables that could predict suicide risk.…”
Section: Discussionsupporting
confidence: 91%
“…This finding reinforces the expression of suicidal ideation as an important marker of psychological distress amongst young people [7]. For most, onset of self-harm occurs in adolescence and international findings have shown an increasing trend in self-harm in young people in recent years [22,23], and there are particular concerns about transgenerational trauma amongst young people in Northern Ireland [24]. Opportunities for early intervention for young people expressing ideation could be an effective suicide prevention target.…”
Section: Discussionsupporting
confidence: 65%
“…Social support system is a crucial protective factor of adolescence suicide [23]. Krystal had made significant efforts to adapt to and survive her poor environment, but most of her efforts were unsuccessful because the social support system that could have helped her did not function properly.…”
Section: Discussionmentioning
confidence: 99%